THE FEATURES OF OPERATION STRATEGY FOR REPAIR OF CITY BRIDGES CONSTRUCTIONS - Bilchenko, A. V.; Kyslov, A. H. (Science and Transport Progress, 2010)
The features of operation of bridge structures as parts of urban transport-and-municipal infrastructure are presented. A strategy for repair of city bridges associated with the change or delay in transportation routes and pedestrian traffic is considered.